CORRUPTION PREVENTION EFFORTS FOR SELECTED VILLAGE HEADS IN KANDAWATI VILLAGE FUND MANAGEMENT TANGERANG REGENCY - Alifa, Asyika Nur; Pertiwi, Dewi; Dumilah, Jelita Retno; Maulana, Maulana; Awalya, Rahmannisa Syifa; Hayat, Nurul (Universitas Tanjungpura, 2023)
The purpose of this research is to find out the social situation of the people of Kandawati Village, Tangerang Regency regarding efforts to prevent corruption in the management of village funds. The method used is qualitative research with a descriptive approach. Meanwhile, data collection techniques were carried out by means of deepening open interviews, namely researchers directly interviewed Mrs. Sumarni as the next elected Village Head in Kandawati Village. The results of this study show that the previous village head in Kandawati Village committed corruption with the motive of being tempted by social fund assistance for people affected by the co-19 pandemic. As a result, the next elected Village Head designed efforts to prevent previous corruption cases by (1) establishing active interaction and communication between the village and the community, (2) often involving the community in village programs, (3) often involving the community in village programs, (4) the need for clear transparency in the management and supervision of Kandawati Village funds. Therefore, with the plans of efforts described by the elected village head, it can minimize the corruption of Kandawati Village funds in Tangerang Regency.